1997
DOI: 10.1177/106591299705000402
|View full text |Cite
|
Sign up to set email alerts
|

New Tests of the Democratic Peace: Controlling for Economic Interdependence, 1950-85

Abstract: 1993) reported that democratic states after World War II were unlikely to engage in militarized disputes with one another, but their continuous measure of joint democracy is problematic. It can decrease if one of a pair of states becomes more democratic, even if the political regime of the other does not change. Thus, results using this index are difficult to interpret. In this study we estimate the likelihood of dyadic conflict using more straightforward indices of joint democracy As in Oneal, Oneal, Maoz, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(32 citation statements)
references
References 53 publications
0
32
0
Order By: Relevance
“…On the other side, numerous studies have found that trade reduces dyadic conflict (Polachek, 1980;Oneal, et al 1996;Oneal and Ray, 1997;Oneal and Russett, 1997, 1999a, 1999b. Several studies have attempted to reconcile the disparate findings in the literature (Gartzke and Li, 2003b), but the debate continues (see Gartzke and Li, 2003c;Oneal, 2003;Barbieri and Peters, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other side, numerous studies have found that trade reduces dyadic conflict (Polachek, 1980;Oneal, et al 1996;Oneal and Ray, 1997;Oneal and Russett, 1997, 1999a, 1999b. Several studies have attempted to reconcile the disparate findings in the literature (Gartzke and Li, 2003b), but the debate continues (see Gartzke and Li, 2003c;Oneal, 2003;Barbieri and Peters, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…difference between the values of democracy (0 to 10) and autocracy (0 to -10) from the Polity III data. Oneal and Ray (1997) argue that the two democracy scores, DEMHI and DEMLO, better capture the political distance between countries than a single additive or multiplicative democracy score. All standardizing variables are also lagged to reduce potential endogeneity.…”
mentioning
confidence: 99%
“…It is not appropriate to assume that what is true at the monadic level should be doubly true at the dyadic level. Care must be taken when operationalizing variables that are meant to capture shared or joint dyadic characteristics (Oneal & Ray, 1997). Nevertheless, our work at the monadic level gives us confidence to proceed to test the dyadic part of Ruggie's argument.…”
Section: Resultsmentioning
confidence: 96%
“…A large and sophisticated literature explores the related question of cross-border economic linkages and their effects on interstate conflict (Bliss & Russett 1998;Keohane & Nye 1989;Oneal & Ray 1997;Oneal et al 1996;Oneal & Russett 1997Polachek 1980Polachek , 1997Polachek et al 1999). 10 Yet, here too the magnitude (Morrow 1999) and/or robustness (Beck, et al 1998) of these relationships has been called into question.…”
Section: Introductionmentioning
confidence: 99%